Inside the White House America's most famous house - Bredar, John B.; Frederickson, Lisa.; National Geographic Society (U.S.). (Washington, DC : Distributed by Warner Home Video, 2003)
This documentary takes viewers on an in-depth tour of the White House, including its private quarters. Interviews with White House staff members as well as every President and First Lady living at the time of production are included, as is a behind-the-scenes look at a state dinner.
Air Force One -- Inside the White House : America's most famous house -- Inside the Pentagon.
Keywords: White House (Washington, D.C.) : -- History